Upaya Meningkatkan Partisipasi Orang Muda Katolik dalam Ibadat tanpa Imam Hari Minggu di Stasi St. Stefanus Kimakamak - Sisilia Ernesliana Kela Kamolen; Scolastika Lelu; Benedikta Yosefina Kebingin (CV. ALIM'SPUBLISHING, 2026)
The participation of Catholic Youth (OMK) in Church liturgy is essential for supporting the Church’s mission and strengthening the faith of the congregation. In stations where the Eucharist cannot be celebrated every Sunday due to a shortage of priests, the Priestless Service becomes an important form of worship while providing opportunities for lay people, including OMK, to take active roles. However, observations indicate that OMK participation in the Priestless Service at St. Stefanus Kimakamak Station, Sta. Maria Goreti Waiwadan Parish, remains limited. This study aims to describe OMK participation, identify factors influencing their involvement, and formulate strategies to enhance their participation. A qualitative approach with a case study design was employed. The participants consisted of ten informants, including four OMK members, the OMK Chairperson, the Station Chairperson, and four congregation members. Data were collected through semi-structured interviews, participant observation, and documentation, then analyzed using the Miles and Huberman model involving data reduction, data display, and conclusion drawing. The findings show that OMK participate as worship leaders, lectors, psalmists, and prayer leaders, although these roles are still dominated by a limited number of active members. Internal factors affecting participation include self-confidence, motivation to serve, faith awareness, and responsibility, while external factors include limited liturgical guidance, digital media influence, and an unsupportive social environment. Participation can be strengthened through liturgical training, faith mentoring, recollections, public speaking training, equal service opportunities, and regular evaluations. Continuous guidance is essential to foster sustainable youth participation and support the regeneration of Church ministers at the station level.